Review on Sustainable Forest Management and Financing in China - World Bank (World Bank, Washington, DC, 2019)
The purpose of this report is to review and disseminate lessons learned from domestically financed forestry programs in China and from those programs financed by international organizations, and to recommend best practices on sustainable forest management. Projects covered by the review include those supported by the World Bank (the Bank), the German Corporation for International Cooperation (GIZ), Kreditanstalt Fur Wiederaufbeau (KfW), and those financed by the Government of China. In addition to conclusions on the most promising models for sustainable forest management (SFM), the review presents an overview of the main sources of financing for SFM and recommendations on what needs to be done to strengthen financial support for SFM. Forests play a key role in the conservation and protection of a wide range of ecosystems, including water courses, watersheds, wetlands, drylands, and deserts. They also serve important functions in conserving on-farm ecosystems, grasslands, and urban environments. Such is the importance of global forest ecosystems that they are often called the ‘the lungs of the Earth,’ the ‘kidneys of the Earth,’ or the ‘immune system of the Earth.’ They are also regarded as pivotal in stabilizing terrestrial ecosystems by balancing and offsetting changes in global dynamics that adversely affect terrestrial ecosystems, such as the sequestration of carbon dioxide.